2011
DOI: 10.1117/12.898478
|View full text |Cite
|
Sign up to set email alerts
|

Detection of fault creep around NAF by InSAR time series analysis using PALSAR data

Abstract: North Anatolian Fault (NAF) has several records of a huge earthquake occurrence in the last one century, which is wellknown as a risky active fault. Some signs indicating a creep displacement could be observed on the Ismetpasa segment. It is reported so far that the San Andreas Fault in California, the Longitudinal Valley fault in Taiwan and the Valley Fault System in Metro Manila also exhibit fault creep. The fault with creep deformation is aseismic and never generates the large-scale earthquakes. But the sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…In İsmetpaşa, central Turkey, a stable aseismic creep (~8 mm/year) was found based on InSAR (e.g., Deguchi, 2011;Kaneko et al, 2013) and Global Navigation Satellite System (GNSS; e.g., Özener et al, 2013) observations. In İsmetpaşa, central Turkey, a stable aseismic creep (~8 mm/year) was found based on InSAR (e.g., Deguchi, 2011;Kaneko et al, 2013) and Global Navigation Satellite System (GNSS; e.g., Özener et al, 2013) observations.…”
Section: 1029/2018gl080984mentioning
confidence: 99%
“…In İsmetpaşa, central Turkey, a stable aseismic creep (~8 mm/year) was found based on InSAR (e.g., Deguchi, 2011;Kaneko et al, 2013) and Global Navigation Satellite System (GNSS; e.g., Özener et al, 2013) observations. In İsmetpaşa, central Turkey, a stable aseismic creep (~8 mm/year) was found based on InSAR (e.g., Deguchi, 2011;Kaneko et al, 2013) and Global Navigation Satellite System (GNSS; e.g., Özener et al, 2013) observations.…”
Section: 1029/2018gl080984mentioning
confidence: 99%
“…[27] To further constrain the inferred friction parameters and the size of the velocity-strengthening layer among the cases with small misfits, we compare the simulated evolution of creep rates to the reported creep rates at Ismetpasa from previous studies (Figure 9) [Ambraseys, 1970;Aytun, 1982;Eren, 1984;Altay and Sav, 1991;Deniz et al, 1993;Cakir et al, 2005;Kutoglu and Akcin, 2006;Kutoglu et al, 2008Kutoglu et al, , 2010Karabacak et al, 2011;Deguchi, 2011;Ozener et al, 2012]. Estimated creep rates reported in the previous studies were based on conventional surveying methods, GPS, LiDAR, or InSAR techniques (Figure 9), Figure 9.…”
Section: Evolution Of Creep Rates Over Timementioning
confidence: 99%
“…He concluded that the creep rate along the Ismetpasa segment was 14 mm/yr in the line of sight [50].…”
Section: Latest Findingsmentioning
confidence: 99%
“…Another work applying InSAR time series analysis for the same region is carried out by Deguchi [50] using Palsar data in order to measure long-term ground deformation from 2007 to 2011. He concluded that the creep rate along the Ismetpasa segment was 14 mm/yr in the line of sight [50].…”
Section: Latest Findingsmentioning
confidence: 99%